Subjective and Objective Dimensions of Turning Points - Daniela Reimer (Social Work and Society, 2014)
The term"turning point" is viewed with great hope. At the same time, it is used with various meanings in research and theory. This leads to a lack of clarity and confusion as to what turning points are. The definitions used in life course research are particularly different to those used in biographical research. This article presents both approaches and lines of research with their specific possibilities and limits. The author proposes using the term"turning point" to cover the interaction of subjective and objective dimensions in people's life courses and biographies. This involves linking biographical research with life course research. A case example from biographical research is used to show how this can be achieved in practice and what new insights can thus be gained.